Mammography Rates for Breast Cancer Screening: A Comparison of First Nations Women and All Other Women Living in Manitoba, Canada, 1999–2008 - Demers, Alain A. (Prev Chronic Dis, 2015)
INTRODUCTION: First Nations (FN) women historically have low rates of preventive care, including breast cancer screening. We describe the frequency of breast cancer screening among FN women living in Manitoba and all other Manitoba (AOM) women after the introduction of a provincial, organized breast screening program and explore how age, area of residence, and time period influenced breast cancer screening participation. METHODS: The federal Indian Registry was linked to 2 population-based, provincial data sources. A negative binomial model was used to compare breast cancer screening for FN women with screening for AOM women. RESULTS: From 1999 through 2008, 37% of FN and 59% of AOM women had a mammogram in the previous 2 years. Regardless of area of residence, FN women were less likely to have had a mammogram than AOM women (relative rate [RR] = 0.69 in the north, RR = 0.55 in the rural south, and RR = 0.53 in urban areas). CONCLUSIONS: FN women living in Manitoba had lower mammography rates than AOM women. To ensure equity for all Manitoba women, strategies that encourage FN women to participate in breast cancer screening should be promoted.